Efeitos na cultura do trigo da rotação com milho e adubos verdes, na presença e na ausência de adubação nitrogenada - Arf, Orivaldo [UNESP]; Silva, Luzia Salustiano Da [UNESP]; Buzetti, Salatiér [UNESP]; Alves, Marlene Cristina [UNESP]; Sá, Marco Eustáquio De [UNESP]; Rodrigues, Ricardo Antonio Ferreira [UNESP]; Hernandez, Fernando Braz Tangerino [UNESP] (Instituto Agronômico de Campinas, 1999)
This trial was carried out at Selvíria county, State of Mato Grosso do Sul, Brazil, on allic, dark red, clayey latosol. The mean yearly is about 1,370 mm and temperature is 23.5oC. The rainfall goal was to evaluate the physical and chemical properties of a soil where corn and green manure were incorporated, with or without N fertilization (35 kg.ha-1) and their effects on wheat crop. The wheat positive response was greater with lab lab and velvet bean in single crop, but there was no response to N fertilization when the crop residues were incorporated to the soil. Physical and chemical properties of the soil were not affected by the treatments.

O presente trabalho foi realizado no município de Selvíria (MS), sob latossolo vermelho-escuro, epieutrófico álico, textura argilosa, precipitação média anual de 1.370 mm e temperatura média anual de 23,5oC. Seu objetivo foi avaliar os efeitos na cultura do trigo e nas propriedades físicas e químicas do solo, da incorporação da fitomassa proveniente de milho, lablabe e mucuna-preta em cultura solteira e intercalada ao milho, na presença e na ausência de adubação nitrogenada (35kg.ha-1). Observou-se resposta positiva do trigo aos adubos verdes, principalmente do lablabe e da mucuna-preta em cultura solteira, e não se obteve resposta à adubação nitrogenada em adição à incorporação da fitomassa dessas culturas, assim como não se caracterizou efeito nas propriedades físicas e químicas do solo.
Wheat crop as affected by the incorporation of corn and green manure to the soil, with and without nitrogen fertilization
Keywords: wheat; green manure; nitrogen; crop rotation; trigo; adubação verde; nitrogênio; sucessão de culturas